1997
DOI: 10.1002/(sici)1097-0142(19970215)79:4<688::aid-cncr5>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the recurrence of hepatocellular carcinoma (HCC) and serum alanine aminotransferase levels in hepatectomized patients with hepatitis C virus-associated cirrhosis and HCC

Abstract: BACKGROUND The relationship between the recurrence of hepatocellular carcinoma (HCC) and the serum alanine aminotransferase (ALT) level was studied in hepatectomized patients with hepatitis C virus (HCV)‐associated cirrhosis and HCC. METHODS Twenty‐six hepatectomized patients with HCV‐associated cirrhosis and HCC whose resected specimens showed neither portal vein nor hepatic vein invasion by HCC histologically were divided into 2 groups: 15 patients who had no recurrence 3 years after surgery (Group A) and 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
87
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(94 citation statements)
references
References 14 publications
5
87
2
Order By: Relevance
“…Tarao and colleagues reported earlier that the cumulative rate of HCCcomplications was higher as the serum transaminase persists at high levels (6). The data in this case indicate that serum transaminase levels also persisted at a high level with multimodalvariations even after the curative treatment of HCC, suggesting the possibility of a recurrence of HCC.…”
Section: Discussionsupporting
confidence: 52%
“…Tarao and colleagues reported earlier that the cumulative rate of HCCcomplications was higher as the serum transaminase persists at high levels (6). The data in this case indicate that serum transaminase levels also persisted at a high level with multimodalvariations even after the curative treatment of HCC, suggesting the possibility of a recurrence of HCC.…”
Section: Discussionsupporting
confidence: 52%
“…The current finding that plasma ADAMTS13 activity or antigen level significantly correlated with serum AST and ALT levels may explain this. Of note, it was previously shown that the higher serum ALT is associated with the higher rate of incidence of HCC development (31) and HCC recurrence after the surgical treatment (32) in HCV-related cirrhosis, suggesting that more hepatocellular damage increases a risk for HCC development in the liver of the same stage of fibrosis. Because plasma ADAMTS13 activity or antigen level reflect hepatocellular damage and subsequent wound healing as well as liver fibrosis stage, plasma ADAMTS13 activity, or antigen level may act distinctly from liver stiffness value in the risk analysis of HCC development.…”
Section: Discussionmentioning
confidence: 96%
“…Moreno et al 23 reported that IFN exhibited remission of liver fibrosis, and control of necroinflammatory process can therefore induce a suppression of the growth process of HCC. Tarao et al 24 reported that high aminotransferase activity resulted in an increase of an HCC recurrence rate in patients with cirrhosis. Our results also suggested that the carcinogenic process in the patients with chronic hepatitis C was greatly enhanced by the aminotransferase fluctuation and its persistence.…”
Section: Discussionmentioning
confidence: 99%